How much do we count? Interpretation and error-making in the decennial census. - Iversen, Roberta Rehner; Furstenberg, Frank F.; Belzer, Alisa A. (Demography, 1999)
In light of the critique of the 1990 U.S. decennial census procedures, a field study was conducted among low-income, inner-city residents in 1991 to analyze how they conceptualized and managed the civic task of census response. It was found that interpretations regarding the purpose and meaning of the census, about commitment to the task, and about connection to government, singly and together with literacy skills, were related to errors that cannot be detected by evaluative methodologies that are employed regularly by the Census Bureau. It is suggested that the validity and reliability of census data, and possibly other self-administered survey research, will be improved by greater use of knowledge about both interpretation and literacy skills in formulating data collection procedures.